PRESTASI PENGEMUDI TRUK ANGKUTAN KAYU DARI BERBAGAI KELOMPOK UMUR (Logging truck drivers' performances at several-age groups) - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
An invelfigation on logging truck drivers' performances was conducted in West Kali1t14ntan Province in 1988. Tfae objective of tile investigation iB to find out the logging truck drivers' performances at several Olle lt1'0UPB.flae driven of Niaan TZ 50 logging trucks at a logging company were observed using time study. To Achieve the lfudy' objective, tile driven were categorized into '(ourgroups based on their age, namely <; 30, > 30-36, > 36-40, and > 40 year& The result of tile study w.,re as follow:1. Logging truck driversat the loggingcompany are relatively old with the age between 30 and 45 years.2. Loging truck driversperformances with